Formulation of process improvement knowledge: 7 components of a good PI story. Issue 1 (5th September 2018) - Norimatsu, So; Endo, Kiyoshi; Usugi, Makoto; Niwa, Aiichiro; Tange, Koichi
Abstract: The authors have been working on establishment of a knowledge structure for process improvement (PI) at "Japan SPI Consortium". Our objective is to store useful knowledge, to provide mechanisms for their usage, and to encourage creation of new knowledge. During our efforts to extract, categorize and consolidate knowledge from the presentation materials at our conferences, we saw problems with respect to the coverage of knowledge expressed in the experiences. To solve this issue, we devised a knowledge model that consists of seven information elements as a representation, and then introduced a standard template to be used when submitting a proposal to the conference. As a result, statistically significant change in the knowledge coverage was observed, and the amount of information has increased for items such as causal analysis, verification and validation of process improvement over the successive conferences. Positive feedback was obtained from proposal reviewers and conference participants for improved understandability. Percentage of successful stories has also increased among the presentations.